Pengaruh Organisasi Industri Dan Struktur Perilaku Kinerja Industri Sekarang Ini - Afifahtus Syaleha; Muhammad Yasin (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research aims to increase knowledge and insight in the field of industrial economics, both in terms of concept, application and development of industrial economics in Indonesia. In order to increase knowledge and insight specifically in the field of industrial organization and business competition, both in terms of concept and implementation. Determine estimates and predictions and what is most likely regarding the company's condition and performance in the future. The research method uses qualitative methods and library research. The data collection technique is to record important information in carrying out data analysis by means of data reduction, data display and drawing conclusions to obtain conclusions. The results of this research show several developments in the industrial sector in Indonesia. The industrial sector is the largest contributor to Indonesia's GDP, especially the manufacturing sector which contributes around 73% of Indonesia's total industrial production. However, the industrial sector in Indonesia is still hampered by several factors, such as poor infrastructure and limited human resources..